2022
DOI: 10.3390/polym14030467
|View full text |Cite
|
Sign up to set email alerts
|

Methods to Characterize Electrospun Scaffold Morphology: A Critical Review

Abstract: Electrospun scaffolds can imitate the hierarchical structures present in the extracellular matrix, representing one of the main concerns of modern tissue engineering. They are characterized in order to evaluate their capability to support cells or to provide guidelines for reproducibility. The issues with widely used methods for morphological characterization are discussed in order to provide insight into a desirable methodology for electrospun scaffold characterization. Reported methods include imaging and ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 152 publications
(201 reference statements)
3
19
0
Order By: Relevance
“…Esophageal epithelial cells proliferate massively on the e-spun membrane, and the cells are closely arranged, displaying excellent cell viability. These results prove the promising potential applications for esophageal repair [21].…”
Section: Resultssupporting
confidence: 60%
“…Esophageal epithelial cells proliferate massively on the e-spun membrane, and the cells are closely arranged, displaying excellent cell viability. These results prove the promising potential applications for esophageal repair [21].…”
Section: Resultssupporting
confidence: 60%
“…Importantly, the diameters of collagen fibers were in the range 72–215 nm, with the electrospun scaffold exhibiting the smallest dimensions. This is particularly relevant given that the in vivo ECM contains fiber diameters ranging from 50 to 500 nm …”
Section: Resultsmentioning
confidence: 99%
“…This is particularly relevant given that the in vivo ECM contains fiber diameters ranging from 50 to 500 nm. 52 Laminin and collagen IV/laminin were then deposited on top of the fibrillar networks showing the formation of a homogeneous film under SEM (Figures S3−S5). Further advanced characterization was done in hydrated biocompatible conditions using multiphoton microscopy (see the next section).…”
Section: Features Of Ecm Models 321 Models Of Connective Tissues and ...mentioning
confidence: 99%
“…Based on the mentioned reasons, atomic force microscopy (AFM) or transmission electron microscopy (TEM) Frontiers in Bioengineering and Biotechnology frontiersin.org are better options for determining the morphology of nanofibers, especially tiny fibers (Ramakrishna, 2005). AFM provides information about the surface of the nanofiber's topographical, morphological, mechanical, and physicochemical properties (Lopez Marquez et al, 2022). It has been reported that scaffold stiffness can modulate cell function and remodeling (Zhu et al, 2019;Yi et al, 2022).…”
Section: Diameter and Size Distribution Of Electrospun Nanofibersmentioning
confidence: 99%
“…Single fiber characterization provides fundamental data for understanding the relationship between nanofiber’s structure and properties. Also, depending on their ultimate utilization, various methods have been developed to characterize nanofiber scaffolds ( Lopez Marquez et al, 2022 ). For example, electrical conductivity and electrochemical reactivity are necessary when nanofibers are intended to be used as sensors ( Liu et al, 2019 ).…”
Section: Characterization Of a Hybrid Nanofibermentioning
confidence: 99%